2011
DOI: 10.3382/ps.2010-01013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Indian native chicken breeds for production, egg and semen quality, and welfare traits

Abstract: The present study was conducted to characterize 2 important native chicken breeds from India and compare them on growth, production, egg and semen quality, and welfare traits. The Aseel breed showed (P < 0.001) higher BW at different ages; higher shank, radius, and toe lengths at 40 wk of age; and greater egg weights at 28, 32, and 40 wk of age than did the Kadaknath breed. The Kadaknath breed reached sexual maturity at an early age, and it had higher 40-wk egg production (P < 0.001). Higher egg specific gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
46
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 9 publications
14
46
3
3
Order By: Relevance
“…In contrast, Anderson et al (2004) reported a significant strain effect on egg shape index which studied with historic strains of single comb white Leghorn chickens. However, our results were supported by Haunshi et al (2011) which observed non-significant differences in the shape index within the native chicken breeds.…”
Section: External Parameterssupporting
confidence: 81%
“…In contrast, Anderson et al (2004) reported a significant strain effect on egg shape index which studied with historic strains of single comb white Leghorn chickens. However, our results were supported by Haunshi et al (2011) which observed non-significant differences in the shape index within the native chicken breeds.…”
Section: External Parameterssupporting
confidence: 81%
“…Effect of genotype on egg quality parameters were reported by various previous workers [5][6][7][8][9]. In general, the egg weight of indigenous birds was found to be low as compared to exotic layers or broilers; however, we observed higher egg weight of Nicobari crosses than the exotic varieties/strains in this study.…”
Section: Discussionsupporting
confidence: 62%
“…India is home to more than 20 breeds (Panda and Praharaj 2002). Among them Aseel and Kadaknath are becoming progressively more popular as pure and out-crossed lines for their benefits in production traits and resistance to disease (Arora et al, 2011;Haunshi et al, 2011). Aseel breed have its origin in Andhra Pradesh.…”
Section: Introductionmentioning
confidence: 99%
“…In all the three varieties of Kadaknath breed most of the internal organs exhibit intense black colouration which is due to the deposition of melanin pigment in the connective tissue of organs and in the dermis (Rao and Thomas, 1984). Although the Kadaknath has many unique characteristics, they are being neglected because of its poor production potential Haunshi et al, (2011). Even though indigenous or native stock show a poor performance relative to highly selected commercial lines, they have the ability to survive in challenging environments (Crawford and Christman, 1992).…”
Section: Introductionmentioning
confidence: 99%